The Effects of Combined Therapy With Metformin and Hydroxypropyl-β-Cyclodextrin in a Mouse Model of Niemann-Pick Disease Type C1 - Du, Jiang; Liu, Xinlei; Zhang, Yan; Han, Xiaojing; Ma, Chunya; Liu, Yanli; Guan, Lihong; Qiao, Liang; Lin, Juntang (Frontiers in Pharmacology, 2022)
Niemann–Pick disease type C1 (NPC1) is a neurodegenerative disorder characterized by lysosomal storage of free cholesterol. 2-Hydroxypropyl-β-cyclodextrin (HPβCD) is a cyclic oligosaccharide derivative that is being developed to treat NPC1. Recently, metformin was reported to be beneficial in various neurodegenerative diseases, such as Alzheimer's and Huntington's diseases. In this study, we examined the effects of combined treatment with HPβCD and metformin on Npc1-/- mice. Unfortunately, body weight and survival rates showed that cotreatment with metformin did not extend survival time of HPβCD-treated Npc1-/- mice. However, cotreatment with metformin reduced inflammatory response and inhibited the proinflammatory cytokine release in the brain, liver and spleen of HPβCD-treated Npc1-/- mice. Furthermore, metformin did not reduce the free cholesterol levels in Npc1-/- brain tissue or fibroblasts. In conclusion, our results demonstrate that metformin does not show beneficial effects on body weight or survival time but reduced the inflammatory response in a mouse model of NPC1 when combined with HPβCD.